Pope Francis and Catholic Social Teaching on Ecology. - Guitián, Gregorio (Worldviews: Global Religions, Culture & Ecology, 2018)
In his visit to the United States, Pope Francis stressed the Christian message on ecology, which includes a calling to an “ecological conversion”. However, a recent paper on the influence of Christian religiosity on managerial decisions concerning the environment argues that Christian faith discourages managers’ environmental-friendly decisions. Francis message on ecology is part of the Catholic Social Teaching (CST), which contains valuable contributions, but it is still to be known. We present a synthetic view of CST on ecology and its implications for businesses, shareholders and consumers, which can also interest non-Christians concerned with the natural environment. Ultimately, we want to explain why Christians involved in economic activity should be concerned with the natural environment. We offer a moral qualification of acts regarding the natural environment, and conclude with some observations for Christian churches and business schools.